Livelihoods vulnerability of climate variability and coping mechanism: the case study of bale lowlands south eastern, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2019)
Climate variability and vulnerability have a range of impacts on livelihood. It is likely that food insecurity will progress more rapidly with rising temperatures and variable rainfall. Hence, the aim of this study is to assess to assess climate vulnerability on livelihoods, and coping mechanism in selected three Woredas’ of Bale lowland, Sothern Western, Ethiopia. The study was conducted in Six PA’s of the Rayitu, Dawe Qachen and Guradamole Woreda in order to achieve these objectives, the study collected data from primary and secondary sources. The primary data collected by using data gathering tools such as FGDs (6), key informant interviews (50) and household survey (436). The study finding showed that the fluctuation of climate makes the on livelihood of the pastoralist community vulnerable in affecting their crop and livestock productivity of the pastoralists’ community. Furthermore, the finding of the study also showed that there have to be an appropriate adaptation mechanism to the changing and fluctuating climate as well as it increases pastoralists community awareness about mechanism by which climate variability to reduce the impact and also to increase institutional involvement with different intervention mechanism. The vulnerability of climate fluctuation exacerbated by lack of adaptation and commitment from both pastoralists and local institutions. Since pastoralists are prioritizing their immediate benefits rather than sustainable development. To cope with the vulnerability the societies use saving, migration diversification, dissemination of technology and provision of safety nets to some lowlanders and emergency aid is among the coping mechanism provided by the government institution. Based on the findings and results of the study, the following recommendations suggested minimizing the vulnerability of the pastoral communities. Improve agricultural production, build on existing people’s knowledge and practices, strengthen local capacity to manage risks through local civil society organizations, foster institutional linkages for livelihood sustainability, and improve the coverage and quality of climate data.Int. J. Agril. Res. Innov. & Tech. 9 (1): 23-34, June, 2019